Elastic modulus prediction based on thermal conductivity for silica aerogels and fiber reinforced composites. Issue 5 (1st March 2022) - Bi, C.; Tang, G.H.; He, C.B.; Yang, X.; Lu, Y.
Abstract: The speed of sound is a critical parameter in the test of mechanical and thermal properties. In this work, we proposed a testing method to obtain the elastic modulus of silica aerogel from the sound speed formulas. The solid thermal conductivity of the silica aerogel is experimentally measured for predicting the sound speeds, and then the elastic modulus is calculated based on the elasticity sound speed model. The experimental data of the solid thermal conductivity of silica aerogels with different densities are employed and the obtained elastic modulus is fitted as a power-law exponential function of the density. Two existing sound speed models and three groups of available experimental data are also employed to validate the present fitting relation, and good agreement is obtained for the silica aerogel in the density range of 150–350 kg/m 3 . The fitting formula can also be extended to estimate the elastic modulus of the glass fiber-reinforced silica aerogel composite. The results show that the elastic modulus of the aerogel composite is sensitive to the glass fiber volume fraction, while the thermal conductivity is weakly dependent on the glass fiber volume fraction at room temperature in the studied range of fiber volume fraction.